Mini review: physically active schools as an arena for promoting health and cognition at the same time - Liersch, Jennifer; Eckenbach, Karin; Pfitzner, Michael (Frontiers in Sports and Active Living, 2025)
Children and young adults spend a large part of their daily lives at school. Due to the increasingly critical physical and mental health of students, various concepts have been developed over the past decades to ensure that physical activity is implemented regularly and wherever possible in everyday school life. Although the relevance of these concepts is widely recognized, physical activities are often cancelled first when time is (suddenly) short. To secure cognitive components, low-movement core subjects are given preference over health-relevant physically active parts. However, there is empirical evidence that targeted integration of physical activity can improve students' cognitive performance, even when the amount of academic core subjects is reduced. The promotion of executive functions through movement has been demonstrated to be a useful approach. The findings of relevant studies are presented and discussed here in relation to different settings in everyday school life, including physical education, extracurricular school sports, and other learning areas. The aim is to demonstrate and justify ways of implementing physical activity in everyday school life and to promote the health and cognitive development of the students at the same time.